Hashemite Kingdom of Jordan : Options for Immediate Fiscal Adjustment and Longer Term Consolidation - World Bank (Washington, DC, 2013)
This report aims to provide options for immediate fiscal adjustment to the government of Jordan and to set the foundations for longer term consolidation. To that effect, an analysis of the dynamics of revenues and expenditures over the years 2000-2011 is undertaken. Specifically, this report attempts to provide options to stop and reverse the declining trend in revenues observed since 2007. Indeed, domestic revenues declined by 9.4 percentage points of GDP between 2007 and 2011. This steady and structural decline in revenues increased the vulnerability of Jordan s public finances to any exogenous shock. Hence, the strong fiscal stress at the eve of the Arab Awakening, due to the pressures to finance widening power sector deficit following the disruption of Egyptian gas supply, and to meet popular demand for additional spending and subsidies. The report also examines: 1) potential sources of savings from current and capital spending, 2) scenarios to reduce power sector deficit including tariff simulations, 3) options to reduce consumer subsidies and target them more efficiently to the poor, and 4) options to reduce the financial deficit of the water sector. The report ranks the measures according to a rating mechanism that takes into account the magnitude of savings, the efficiency improvements in the use of public resources, the distributional impact, previous dynamic of the spending or revenue item in question, the poverty and social impact, and the growth impact. Finally, the report proposes a matrix of policy objectives and actions that identifies areas of policy reform, policy objectives, actions needed to reach this objective, and time horizon.